An Optimization Model for Urban Readjustment and Subdivision Regulations in Turkey - Mehmet Kucukmehmetoglu; Abdurrahman Geymen (European Regional Science Association (ERSA), 2014)
Rapid urbanization in Turkey has resulted in various problems in urban spaces such as squatter houses, substandard subdivisions, and low-quality urban environment. In order to facilitate self-motivated developments, government has enacted various laws and bylaws and made amendments in current legal frameworks. The 18th Article (Dough Rule) of the Land and Building Development Law (İmar Kanunu) has various and extensive applications in regulating and restructuring cadastral properties. One of the major goals of this law and associated bylaw (bylaw on land readjustment) is to prepare standard high quality subdivision lots with regard to zoning plans. However, there are a series of legal and practical difficulties, and legal dilemmas in allocating the properties among various land owners: First, because, neither local nor the central government has financial capability to confiscate private properties for road networks and public land uses, the government proportionally (maximum 40%) confiscates properties without paying the cost of expropriation. Implicitly, the current law assumes that land owners take the monetary advantage of being in the well-designed planned subdivision and having standard lot(s). Second, allocation from cadastral properties to the standard lots neither provides each owner a unique private lot(s) in the planned subdivision, and nor guarantees that every land owner acquires a piece of land in the same location (spot) before the readjustment process. Although there are certain rules for reallocation in the bylaw, the reallocation is open to harsh disputes and often leads to court cases. This study develops a new approach to reallocate properties to minimize the adversaries and maximize the property owners' desires. The developed optimization technique, first, considers the main principles of the bylaw, and second, finds the best allocation solution for relevant property owners. As an illustrative example, one of the allocation problem is revisited and the difference between model and actual case is reviewed. It has been understood that the developed optimization technique is a practical tool for this kind of problems.
Keywords: R00; 330